1079. The Risk of Cytomegalovirus (CMV) Infection and Recurrence Among Solid Organ Transplant Recipients. (31st December 2020) - Reekie, Joanne; Khurana, Mark P; Lodding, Isabelle P; Ekenberg, Christina; Gustafsson, Finn; Helleberg, Marie; Mocroft, Amanda; Perch, Michael; Rasmussen, Allan; Sørensen, Søren S; Lundgren, Jens
Abstract: Background: Solid organ transplant (SOT) recipients are at a high risk of developing cytomegalovirus (CMV) post-transplant (tx) with many experiencing a recurrence shortly after clearing the first episode. We aimed to identify risk factors associated with CMV infection and recurrence. Methods: SOT recipients (≥ 18 years) transplanted between 2011-2016 were investigated for factors associated with CMV infection within 1 year from baseline and recurrent CMV within 6 months of stopping CMV treatment for the first infection using cumulative incidence curves and Cox proportional hazards models. Baseline was defined as either tx date or date of stopping CMV prophylaxis for those initiating CMV prophylaxis within 7 days of tx. Individuals with breakthrough CMV while on prophylaxis were excluded (n=29). Figure 1 Risk of CMV infection in 755 SOT recipients in the first year from baseline, stratified by CMV serostatus. Baseline was defined either the date of transplant (n=285) or stopping CMV prophylaxis (n=470). Figure 2 Factors associated with CMV infection in the first year from baseline. Baseline was defined either the date of transplant (n=285) or stopping CMV prophylaxis (n=470). Results: We included 755 SOT recipients, 173(23%) developed CMV infection within one year of baseline with CMV disease present at diagnosis in 17% of the cases. The risk of CMV infection was lower in patients with low (aHR 0.19, 95%CI 0.12-0.29) and intermediate (aHR 0.26, 95%CI 0.18-0.36) risk CMV IgG serostatus compared to high risk (Figure1). Liver and lung tx, female sex, older age and year of tx were also associated with an increased risk of CMV infection (Figure 2). Among the 470 (62%) patients who received CMV prophylaxis those who received < 85 days had a higher risk of CMV infection than those receiving ≥ 85 days (aHR 1.80, 95%CI 1.19-2.72). 99 recipients were investigated for recurrent CMV; 40 (40%) experienced relapse within 6 months of stopping treatment for their first infection. The risk of recurrent CMV was significantly lower in those with low (aHR 0.20, 95%CI 0.06-0.74) and intermediate risk serostatus (aHR 0.40, 95%CI 0.19-0.84) (Figure 3). Older age (aHR 1.23 per 5 years older, 95%CI 1.06-1.44) was also significantly associated with recurrent CMV infection (Figure 4). Figure 3 Risk of recurrent CMV infection in the 6 months following clearance and stopping of treatment for the first CMV infection (N=99), stratified by CMV serostatus at the time of transplant Figure 4 Factors associated with recurrent CMV infection within 6 months of stopping treatment for the first CMV infection Conclusion: Recurrent CMV infection remains a significant complication among SOT recipients, especially in those with high risk CMV IgG serostatus. These findings highlight the necessity to successfully treat and monitor this subgroup following their first infection. Novel medical interventions and strategies to prevent CMV infection are of particular importance to this high risk group. Disclosures: All Authors : No reported disclosures